2021
DOI: 10.1155/2021/8515607
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Usual Nutrient Intake of Filipino Children Aged 6–12 Years in Selected Areas in the Philippines: A 2018 National Nutrition Survey

Abstract: Background. This study aimed to determine the prevalence of vitamin D deficiency, usual nutrient intake, and food sources of vitamin D of Filipino children aged 6–12 years in selected areas in the Philippines. Methods. The National Nutrition Survey (NNS) collected blood samples of children aged 6–12 years from selected study sites: Manila City and Quezon City in the National Capital Region (NCR); Cagayan Province and Baguio City in Luzon; Northern Samar and Siquijor in Visayas; and Butuan City and Sultan Kudar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This result is similar to data from the 2013 National Nutrition Survey for Filipinos, which showed a 54% prevalence of combined vitamin D insufficiency and deficiency in the National Capital Region of the Philippines. 34 A 2015 study by Chin done in Malaysia, another Southeast Asian country, 15 showed that 23% of the participants were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to data from the 2013 National Nutrition Survey for Filipinos, which showed a 54% prevalence of combined vitamin D insufficiency and deficiency in the National Capital Region of the Philippines. 34 A 2015 study by Chin done in Malaysia, another Southeast Asian country, 15 showed that 23% of the participants were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 99%